Crewing services of manning companies in the Philippines: A review of compliance to International Chamber of Shipping Manning Agency Guidelines - Sep A. Cabangon; Dhuff Mattheus Ortiz (International Journal of Academe and Industry Research, 2025)
This study examines the compliance of a Metro Manila-based manning agency with the International Chamber of Shipping (ICS) guidelines, specifically the Maritime Labour Convention (MLC) 2006. The research focuses on the effectiveness of crewing services and their alignment with international standards. Survey results suggests strong agreement (M=4.59) that crewing managers effectively fulfill their responsibilities, particularly in overseeing medical requirements, travel arrangements, and compliance with flag state laws. The highest-rated responsibilities were compliance with flag state laws (M=4.66) and managing travel arrangements (M=4.67). Further analysis assesses the alignment of agency practices with MLC 2006 standards, yielding a strong overall mean score (M=4.59). Key compliance areas, such as the absence of recruitment fees and certificate validation, were rated highly, while placement services received a slightly lower rating (M=4.44), indicating room for improvement. Regression analysis confirms that alignment with MLC 2006 standards significantly predicts the fulfillment of agency obligations (R²=0.67, p<0.001), whereas mere compliance does not (β=0.044, p=0.462). This suggests that agencies must integrate international frameworks into operations rather than only meeting local regulatory minimums. Future research should explore how these standards influence agency performance in various maritime contexts. In conclusion, the studied manning agency demonstrates strong compliance with ICS and MLC 2006 guidelines, distinguishing it from other agencies facing recruitment inefficiencies and workforce retention challenges.